Evaluation of the antiproliferative activity of 106 marine microbial metabolites against human lung cancer cells and potential antiproliferative mechanism of purpuride G. (1st May 2021) - Ge, Hengju; Shi, Muran; Ma, Mingzhu; Lian, Xiao-Yuan; Zhang, Zhizhen
Graphical abstract: Abstract: A total of 106 marine microbial metabolites were evaluated for their antiproliferative activity against human lung cancer cells. Results showed that 23 compounds exhibited activity in inhibiting the proliferation of A549 and H157 cells with IC50 values ranging from 1.5 to 48.2 μM. Pyrrospirone F, chrysophanol, physcion, and purpuride G are the four most active compounds with IC50 values of 1.5–7.3 μM. Further investigation of purpuride G (a newly discovered sesquiterpene lactone) demonstrated its potent antiproliferative activity against six different lung cancer cells of A549, H157, H460, H1299, H1703, and PC9 with IC50 values of 2.1–3.3 μM. The antiproliferative activity of purpuride G against cancer cells is related to block cell cycle, induce apoptosis through regulating the apoptotic proteins Bcl-2 and Bax, and inhibit glycolysis by downregulating two key glycolytic enzymes of hexokinase 2 and pyruvate kinase M2.